Estimated Loss of Lifetime Employment Duration for Patients Undergoing Maintenance Dialysis in Taiwan. Issue 5 (8th May 2021) - Chang, Yu-Tzu; Wang, Fuhmei; Huang, Wen-Yen; Hsiao, Hsuan; Wang, Jung-Der; Lin, Chang-Ching
Visual Abstract: Abstract : Background and objectives: An accurate estimate of the loss of lifetime employment duration resulting from kidney failure can facilitate comprehensive evaluation of societal financial burdens. Design, setting, participants, & measurements: All patients undergoing incident dialysis in Taiwan during 2000–2017 were identified using the National Health Insurance Research Database. The corresponding age-, sex-, and calendar year-matched general population served as the referents. The survival functions and the employment states of the index cohort (patients on dialysis) and their referents for each age strata were first calculated, and then extrapolated until age 65 years, where the sum of the product of the survival function and the employment states was the lifetime employment duration. The difference in lifetime employment duration between the index and referent cohort was the loss of lifetime employment duration. Extrapolation of survival function and relative employment-to-population ratios were estimated by the restricted cubic spline models and the quadratic/linear models, respectively. Results: A total of 83, 358 patients with kidney failure were identified. Men had a higher rate of employment than women in each age strata. The expected loss of lifetime employment duration for men with kidney failure was 11.8, 7.6, 5.7, 3.8, 2.3, 1.0, and 0.2 years for those aged 25–34, 35–40, 41–45, 46–50, 51–55, 56–60, and 61–64 years, respectively; and the corresponding data for women was 10.5, 10.1, 7.9, 5.6, 3.3, 1.5, and 0.3 years, respectively. The values for loss of lifetime employment duration divided by loss of life expectancy were all >70% for women and >88% for men across the different age strata. The sensitivity analyses indicated that the results were robust. Conclusions: The loss of lifetime employment duration in patients undergoing dialysis mainly originates from loss of life expectancy.